Sensitivity of Premium Calculations to Distribution Assumptions: The Impact of Using Pareto vs. Pareto Distributions Exponential on Claims of Large Losses - hadiat, aisha; Anjani, Niken Pinkyvita Nur (International Journal of Global Operations Research, 2025)
Premium calculation is a fundamental aspect of the insurance industry to ensure the sustainability and profitability of companies. One of the main factors that affect the accuracy of premium calculation is the selection of claim probability distribution, especially for large claims that have the potential to cause significant losses. Exponential distribution is often used because of its simplicity, but its light tail characteristic makes it less suitable for modeling extreme claims. Conversely, the Pareto distribution, with its heavy-tailed nature, is considered more representative in capturing the risk of large claims. This study aims to analyze the sensitivity of premium calculations to distribution assumptions by comparing the use of exponential and Pareto distributions on large loss claim data. This analysis is expected to provide a practical overview of the impact of distribution selection on premium setting and its implications for insurance risk management in Indonesia.